From Enron to Evo: Pipeline Politics, Global Environmentalism, and Indigenous Rights in Bolivia - Hindery, Derrick; Hecht, Susanna B (University of Arizona Press, 2013)
Throughout the Americas, a boom in oil, gas, and mining development has pushed the extractive frontier deeper into Indigenous territories. Centering on a long-term study of Enron and Shell's Cuiabá pipeline,From Enron to Evotraces the struggles of Bolivia's Indigenous peoples for self-determination over their lives and territories. In his analysis of their response to this encroaching development, author Derrick Hindery also sheds light on surprising similarities between neoliberal reform and the policies of the nation's first Indigenous president, Evo Morales.Drawing upon extensive interviews and document analysis, Hindery argues that many of the structural conditions created by neoliberal policies-including partial privatization of the oil and gas sector-still persist under Morales. Tactics employed by both Morales and his neoliberal predecessors utilize the rhetoric of environmental protection and Indigenous rights to justify oil, gas, mining, and road development in Indigenous territories and sensitive ecoregions.Indigenous peoples, while mindful of gains made during Morales's tenure, are increasingly dissatisfied with the administration's development model, particularly when it infringes upon their right to self-determination.From Enron to Evodemonstrates their dynamic and pragmatic strategies to cope with development and adversity, while also advancing their own aims.Offering a critique of both free-market piracy and the dilemmas of resource nationalism, this is a groundbreaking book for scholars, policy-makers, and advocates concerned with Indigenous politics, social movements, environmental justice, and resistance in an era of expanding resource development.